Basement-cover relationships and metamorphic patterns in the foreland of the Torngat Orogen in the Saglek-Hebron area, Labrador - Ryan, Bruce (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1990)
Summary The Archean Nain Province of northern Labrador displays a variable imprint of Early Proterozoic thermotectonism several tens of kilometres east of its collisional boundary (Torngat Orogen) with the Archean Rae (eastern Churchill) Province, the latter extensively reworked by Early Proterozoicevents. This imprint is discerned by the west-ward increase in metamorphic grade in the Early Proterozoic Domes diabase dykes and from the degree of retrogression of Archeangranulite-facies gneisses. Early Proterozoictectonic effects also include the translation of Raman Group cover rocks over their Ar-chean basement, and the subsequent folding of both the basement décollement and the cover. Later steep reverse faults dissect the boundary zone between the Rae (Churchl) Province and the Archean foreland. All these features are believed to be related to Earty Proterozoic oblique continental collision between two Archean crustal blocks.